Karakteristik Beton Scc (Self Compactibility Concrete) dengan menggunakan Limbah Kaca dan Limbah Bauksit sebagai Bahan Tambah - Etty Rabihati; Rasiwan Rasiwan; Deny Syahrani (Politeknik Negeri Pontianak, 2020)
The use of SCC (Self Compactibility Concrete) concrete in Indonesia is increasing in the field, especially for a variety of buildings that require large compaction speeds or use concrete that can compact itself. SCC Concrete Technology in the construction industry is growing, especially in meeting the needs of the construction world. Added material is an alternative material used to increase the strength characteristics of the concrete. Likewise the addition of glass powder waste, and bauxite waste in making SCC concrete is expected to increase the compressive strength concrete. Fresh concrete, which belongs to the self-compacting concrete (SCC) group, has a very high slump value (more than 20 cm), so measurements with cone abrams are no longer effective. The use of these materials as substitute materials and added based on the thought to utilize glass waste and , bauxite waste in order to reduce the impact of environmental pollution and provide economic value. This study uses glass powder as glass waste and bauxite waste as added material for cement. This study uses four kinds of mixed compositions, namely 0% (ordinary concrete); 2.5% mixture; 5% and 7.5% by weight of cement as added material from glass waste and bouksit waste, where each composition consists of 3 cylindrical specimens with a diameter of 15 cm and a height of 30 cm. Until now there has never been any research from mananpun to test the 2 (two) mixtures, therefore we want to test it so that glass waste and bauxite waste are not wasted and can be reused, especially in making SCC concrete. From the research results it was found that the maximum slum cone test results were in the 2.5% variation that is equal to 44.3 cm, while the minimum at 0% was 29.3 cm. The maximum compressive strength at the age of 3 days is 455,418 kg / cm2 for variations of 7.5% while the minimum is at a variation of 2.5% of 200.469 kg / cm2 at 7 days of concrete.